Research on the negative effect of product scarcity appeals on the purchase intention of green products and its mechanism - Ye, Shenghong; Liu, Guangrui; Lin, Yanfeng; Lin, Zhiheng; Shi, Yijing; Huang, Zan (Frontiers in Psychology, 2024)
Studies have shown that product scarcity appeals affect consumers’ perceived scarcity, willingness to pay, and other responses, and that scarcity appeal has the potential to cause consumers to pay higher attention to the product. However, there is a lack of research on the psychological responses of consumers to scarcity appeal from the perspective of perceived green washing. In this paper, three experiments are conducted to demonstrate the impact of product scarcity appeals on consumers’ purchase intentions. The research shows that when green products use product scarcity appeals as a strategy, consumers’ purchase intentions are affected, but consumers’ information processing about the product is the most important determinant. Perceived green washing mediates the negative effect of product scarcity appeals on green product purchase intentions. And impression management motives moderate the negative effect of product scarcity appeals on green product purchase intentions. The findings of the study not only help companies to effectively adopt the right advertising strategies to improve their marketing effectiveness, but also help them to explore the market for green products.